Elementary english language instruction: colombian teachers’ classroom practices (2004)
An in-progress ethnographic research project about teachers who are facing the complex task of teaching English to children in 7 public elementary schools in the metropolitan area of Medellin is presented in this article. First, the need for this research is outlined by researchers; second, the methodology of the project is described; third, up-to-date findings which include a profile of the 12 teachers who are participating in this study, and an analysis of their class methodology in terms of activities, materials, teacher and student roles are reported. Lastly, implications of this research project related to early foreign language instruction are highlighted. Key words: Public Elementary-English-Language Instruction, English-Foreign Language, Ethnography-Research-Method, Teaching-Methodology Este artículo presenta los resultados preliminares de una investigación etnográfica acerca de las estrategias metodológicas utilizadas por profesores de básica primaria que enseñan inglés como lengua extranjera en 7 escuelas públicas del área metropolitana del municipio de Medellín. En la primera parte se resalta la importancia de esta investigación en nuestro medio y en la segunda, de los 12 profesores participantes y un análisis de la metodología empleada por ellos con respecto a las actividades de clase, los materiales y el rol del estudiante y del profesor. Finalmente, se discuten algunas de las implicaciones de este proyecto de investigación en la enseñanza de lenguas extranjeras a niños. Palabras claves: Inglés-Enseñanza-Básica Primaria, Lengua Extranjera-Inglés, Estudio Etnográfico-Investigación, Enseñanza-Metodología